ANALISIS PENERBITAN OBLIGASI DAERAH SEBAGAI ALTERNATIF PEMBIAYAAN PEMBANGUNAN PADA PEMERINTAH PROVINSI KALIMANTAN TIMUR - Imam Nazarudin latif., Habib Mahrufi, Titin Ruliana, (EKONOMIA, 2016)
The purpose of this research is to know of solvability of the east kalimantan province goverment in issuing municipal bond as alternative financing development. Analysis tool that is being used is governance regulation no. 30 year 2011 about regional loan and ministry of finance regulation no. 153/PMK.07/2015 about maximum limit of APBD cumulative deficit, maximum limit deficit of APBD, and maximum limit of cumulative regional loan on 2016.Result of this research is the province governance of east kalimantan can issuing municipal bond up to Rp6.934.706.516.907,01 and ability tmo pay the principal instalment and loan interest amount of Rp3.228.693.392.637,84, with the ability to pay 47 % of total loan every year, then governance province of east kalimantan have solvability high enough. So, governance province of east kalimantan has fulfillÂ  the criteria to issuing municipal bond.